A Study of Strategies Used in Translating the Names of Skills and Battle Powers from Chinese to Thai in the Chinese Fantasy Anime Entitled ‘Soul Land’ (斗罗大陆) - Pasaja, Jiraporn; Numtong, Kanokporn (Ganesha Journal, 2024)
This article aimed to study strategies for translating the names of skills and battle powers in the fantasy anime entitled ‘Soul Land’ from Chinese to Thai. The names of skills and battle powers were collected from the subtitles translated from Chinese into Thai in the Soul Land anime’s seasons 1-4, episodes 1-264 broadcasted via the WeTV application. A name list form was adopted as a tool to collect data and classify translation strategies. The data was described by descriptive analytics. The findings showed that there were totally 509 skill and battle power names which were translated from Chinese into Thai. There were 3 translation strategies employed: 1) meaning translation (420 names or 82.51%), 2) combination of meaning translation and transcription or transliteration (26 names or 5.10%); and 3) generating new names based on the original (63 names or 12.37%). The most commonly used strategy among the translators was found to be the meaning translation in order to be convey the meanings which were easy for audiences to understand and the translators avoided the unnecessary transcription or transliteration because of three factors: 1) the past influence of Chinese martial arts-based movies over the present, 2) the association between use of translation strategies and generation of skill and battle power names, and 3) the tendency to use Mandarin for transcription or transliteration of proper names. Three types of translation errors were found: 1) incorrect translation of meanings, 2) selection of translated words with a unity lack, and 3) word misspelling caused by incorrect use of tone marks due to 2 factors: 1) translations in each episode carried out by different translators without discussion and agreement on using identical words in the entire series, and 2) lack of checking translated subtitles for accuracy.